Comparison of Table Bearing Capacity for Different Types of Foundation Soils / Rocks - NEUMAN, David; SOMBATHY, Erik; VLČEK, Jindřich; MATUSZKOVÁ, Barbara (GeoScience Engineering, 2022)
The aim of the publication was to compare the suitability of foundation soils on the basis of table (standard empirical) bearing capacity. Four basic groups of foundation soils were compared, which are fine-grained soils, sandy soils, gravelly soils and rocky soils. The scientific motivation for this comparison is that visualizing the difference between the suitability and unsuitability of a particular foundation soil / rock is one of the fundamental problems in engineering geology. Quantifying and visualizing the differences is very important for understanding the significance of different geological settings. Of all the foundation soil classes evaluated, the R1 rock soil group with a simple compressive strength greater than 150 MPa and a discontinuity distance greater than 600 mm achieves the highest table bearing capacity of 8 000 kPa. In contrast, the lowest table bearing capacity is achieved by the class of fine-grained foundation soils (F8) of clays with extremely high plasticity and soft consistency, where the value of this class is only 40 kPa. Keywords: Fine-grained soils; Gravelly soils; Rock mass; Sandy soils; Table bearing capacity.